Researching the authoritarian: a conversation on methodology and ethics in closed contexts - Wolfe, Sven Daniel; Kuletskaya, Dasha (Copernicus GmbH, 2026)
In this academic conversation we reflect on authoritarianism and its implications for research and researchers. Framed within the global authoritarian turn, the conversation explores a variety of practical, methodological, and ethical challenges of researching authoritarian politics, practices, and spaces. Specifically, we discuss losing field access due to repression or violence, followed by a reliance on secondary materials; the censorship or closure of media and the challenges of working with ephemeral digital material; and the declining reliability of sources due to manipulation, silencing, and displacement. These conditions force researchers to consider when data become too compromised to continue inquiry while simultaneously highlighting ethical dilemmas about protecting vulnerable contacts – including from repressive state practices that shift over time and create new vulnerabilities. The conversation contributes to the burgeoning literature on research in authoritarian contexts and argues that audiences from the broader West have much to learn from those in the post-socialist East.